O professor do atendimento educacional especializado na sala de recurso multifuncional (AEE/SRM) com formação em psicopedagogia: atuação junto ao aluno com Transtorno do Espectro Autista - TEA - Dornelas, Cristina dos Reis Souza (2024)
ABSTRACT This study, carried out in the master's and doctoral programs at the Faculty of Education of the Federal University of Uberlândia (UFU), in the research line of Educational Knowledge and Practices, has as theme: "The Specialized Educational Care teacher in the Multifunctional Resource Room (SEC/MRR) with training in Psychopedagogy: working with students with Autism Spectrum Disorder (ASD)". Thus, the object of the research is the contributions of Psychopedagogy to proposing inclusive practices for students with ASD in the context of the SEC/MRR. Based on the object, the study's problematizing questions were listed: how does the SEC/MRR professional, trained in Psychopedagogy, work with students with ASD? Is the work of the SEC/MRR professional, trained in Psychopedagogy, with the student with ASD, inclusive? Does the work of the SEC/SRM professional, trained in Psychopedagogy, with the student with ASD, correspond to psychopedagogical foundations and principles? Based on the object of study and the problematization, the general objective of the research is to analyze the work of the professional in the SEC/MRR, with training in Psychopedagogy, with the student with ASD, identifying whether the practices carried out are inclusive and correspond to the psychopedagogical foundations and principles. Considering the location and time frame, the specific objectives consist of analyzing: the possibilities and impossibilities of inclusion, based on the work of the SEC/MRR professionals; whether there is a correlation between the foundations and principles of Psychopedagogy; and the practice of the research participants. The methodology guiding the work is qualitative, exploratory in nature, and seeks to respond to the problematization and the desired objectives. The research was carried out in the city of Coromandel-MG, in two schools, specifically in the SEC/MRR, with two teachers trained in Psychopedagogy who work with students with ASD. The instruments used to collect the data were: Semi-structured Interviews and Document Analysis. In order to understand whether the work of teachers trained in Psychopedagogy is inclusive and whether it corresponds to psychopedagogical foundations and principles, it was necessary to address, in the light of the theoretical framework, the historical construct of Psychopedagogy, its concept, object of study, objectives, clinical and institutional configuration and its possibilities in the school context. It also covered the importance of heterogeneity in the SEC/MRR modality and the legislation that supports and defines work in this environment with its target audience, emphasizing ASD, with its historical and conceptual aspects, as well as diagnosis, intervention and schooling policy. In the analysis, the data was organized into two categories, the first of which deals with the work of the SEC professional in the MRR space and their considerations about the possibilities and impossibilities of inclusion. The second category analyzed the foundations and principles of Psychopedagogy in the context of the SEC/MRR with students with ASD, considering psychopedagogical knowledge and its contribution to the school team, the family and, above all, the student. Thus, it was concluded that the SEC/MRR is a suitable environment for teachers trained in Psychopedagogy to work in the inclusion of students with ASD. To this end, the study revealed the need for this professional to constantly invest in training according to the knowledge acquired from Psychopedagogy in order to intervene throughout the teaching and learning process, including acting as a mediator between the parties - school and family.